Pengaruh Kualitas Pelayanan Dan Harga Terhadap Keputusan Pembelian Layanan Internet MNC Play Media Semarang - Salasa Widagda; Apriatni Endang Prihatini (Jurnal Ilmu Administrasi Bisnis, 2019)
The number of internet users continues to increase, in order to access the internet users must subscribe to internet service providers, one of which is MNC Play Media. MNC Play Media Semarang experienced a decrease in the percentage of sales targets from 2015 - 2017 and never been nominated for the TBI award in the Fixed ISP category from 2014 - 2017. According to APJII the factors that influence ISP selection are service quality and price. This study aims to determine the effect of service quality and price on purchasing decisions. The type of research is explanatory research and sampling using the nonprobability sampling technique purposive sampling method, collecting data using the google docs questionnaire. The number of samples used was 100 respondents from Semarang City. This study uses quantitative and qualitative analysis with validity, reliability, correlation coefficients, coefficient of determination, simple and multiple regression, significance of t test, and F test. The results of the study show that service quality and price variables have a strong and positive influence on purchasing decisions. Service quality and price variables show 0.651 that the relationship between the two variables to purchasing decisions has a strong relationship. The service quality variable in the determination test (R square) shows 35.7% influence purchasing decisions, so 64.3% is influenced by other factors. The price variable in the determination test (R square) shows that 23.6% affects purchasing decisions, so 76.4% is influenced by other factors.